G105(P) Initiative to improve clinical coding for patient admission episode (inpatient) by recording patient co-morbidities. (25th October 2020) - Joshi, M; Bandi, S; Ball, R
Abstract : Background: We reviewed benchmarking data about comorbidities in paediatric medicine provided by Civil Eye Research compared to other tertiary hospital. The data showed that our hospital (paediatric medicine) was on the lowest spectrum compared to other hospitals of similar size. This prompted us to look it in depth with an aim to improve our recording of co-morbidities and clinical coding. Aim: To record patient co-morbidities during each admission episode. Methods: We applied Quality Improvement (QI) methodology (PDSA cycle- Plan, Do, Study, Act) in this project. Coding champion's role helped to bridge the gap between clinical coding and the medical teams. We identified relevant co-morbidities and designed a paediatric co-morbidity sheet. These sheets were formally launched on all the paediatric wards and medical & nursing staff was updated via regular teaching and educational sessions. We completed one audit cycle by retrospectively reviewing 20 patient medical notes each time (May-June 2019 &amp August-September 2019). Results: Our first audit showed that only 20% (4/20) patient notes had a co-morbidity sheet whereas the re audit post educational sessions helped to improve it to 75% (15/20). Since implementing the co-morbidity sheet and using it regularly from April 2019, our low bracket coding (between 0–1 co morbidity) reduced from 40% to 27%; mid bracket coding(2–5 comorbidities) improved from 47% to 54% and the highest bracket coding(6+ co morbidities) improved from 13% to 19%. Overall this resulted in a financial gain of £195, 000 since the implementation of co-morbidity sheet. Conclusion: Comorbidities are conditions that are present in association with a current illness with which a patient is admitted. It is very important to document comorbidities in clinical notes and discharge summaries which can then be coded accurately. This in turn helps to secure appropriate funding to provide appropriate and effective patient care. Our experience shows that using a comorbidity sheet based on common health conditions helps clinical as well as coding staff to improve clinical coding. Regular updates via educational sessions about the benchmarking data and PDSA cycles are key to sustain this improvement.